Lateral damage and point of impact in intersection crashes: Implications for injury - Chipman, Mary L.; Lebovic, Gerald; Desapriya, Ediriweera; Gane, John (Assurances et gestion des risques / Insurance and Risk Management)

(untitled) (Faculté des sciences de l’administration, Université Laval, 2006)
Crashes in intersections may result in damage to vehicles and injury to occupants in many different ways. One vehicle hitting the side of another (T-type) is the classic side impact; however, we have argued in the past that other crash configurations (e.g., L-type) may subject occupants to similar risks because both vehicles may sustain lateral damage. To test this assumption, we examined crash data from police reports of 4032 intersection right-angle crashes (IRC), collected by the Insurance Corporation of British Columbia for 2002. We compared the risk and types of injury in target and bullet vehicles for T-type crashes, L-type crashes by front and rear fender involvement and for all other IRC crashes. There were 787 T-type crashes (impact into either side of target vehicle), compared to 798 L-type crashes (impact into front fender) and 350 L-type (impact into rear fender). Overall, injury risk was 23.5%. Proportions injured were very similar for occupants of target and bullet vehicles in T-type crashes (OR = 0.996; 95% ci 0.80 to 1.24.); for L-type crashes, the proportions were 23.2% for front and/or front fender involvement and 15.0% for crashes involving the rear fender of one vehicle and the front or front fender of the other (OR =1.71; 95% ci 1.40 - 2.10). Apart from rear fender crashes, proportions injured were very similar (P > 0.05). Other factors, notably weather, lighting, land use and vehicle damage differed significantly by crash type, and were strongly associated with injury risk. Since rear-fender crashes are a small proportion of IRC crashes, this suggests that it is not necessary to subdivide crashes by configuration in IRC crashes.